2022
DOI: 10.3389/fmed.2022.882891
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Development of Adverse Infusion Reactions to Rituximab in Patients With Systemic Lupus Erythematosus, Rheumatoid Arthritis and Non-Hodgkin's Lymphoma-Enigma Variations

Abstract: It has become clear that rituximab treatment is useful for both B-cell malignancies and autoimmune rheumatic diseases. However this treatment is associated with an increased risk of an allergic reaction. We have reviewed the frequency with which these reactions occur in these different conditions. They appear to be less frequent when rituximab is used to treat rheumatoid arthritis and systemic lupus perhaps because concomitant steroids are invariably given to these patients with the rituximab which is not nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Notably, the rate of IRRs was significantly higher in the former group (25.0-35.9%) compared with the rate in the latter group (9.4-17.5%; P<0.001) ( 11 ). The history of concomitant steroid use before rituximab treatment has been mainly ascribed to the lower incidence of IRRs to rituximab in autoimmune disorders ( 28 ). In the study by Laudati et al ( 19 ), a low incidence of IRRs was found in patients with B-cell NHL treated with dexamethasone premedication in comparison with no dexamethasone pretreatment (19.1 vs. 36.7%; P=0.005).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the rate of IRRs was significantly higher in the former group (25.0-35.9%) compared with the rate in the latter group (9.4-17.5%; P<0.001) ( 11 ). The history of concomitant steroid use before rituximab treatment has been mainly ascribed to the lower incidence of IRRs to rituximab in autoimmune disorders ( 28 ). In the study by Laudati et al ( 19 ), a low incidence of IRRs was found in patients with B-cell NHL treated with dexamethasone premedication in comparison with no dexamethasone pretreatment (19.1 vs. 36.7%; P=0.005).…”
Section: Discussionmentioning
confidence: 99%